Gene expression profiling of soft and firm Atlantic salmon fillet. - Thomas Larsson; Turid Mørkøre; Kari Kolstad; Tone-Kari Østbye; Sergey Afanasyev; Aleksei Krasnov (PLoS ONE, 2012)
Texture of salmon fillets is an important quality trait for consumer acceptance as well as for the suitability for processing. In the present work we measured fillet firmness in a population of farmed Atlantic salmon with known pedigree and investigated the relationship between this trait and gene expression. Transcriptomic analyses performed with a 21 K oligonucleotide microarray revealed strong correlations between firmness and a large number of genes. Highly similar expression profiles were observed in several functional groups. Positive regression was found between firmness and genes encoding proteasome components (41 genes) and mitochondrial proteins (129 genes), proteins involved in stress responses (12 genes), and lipid metabolism (30 genes). Coefficients of determination (R(2)) were in the range of 0.64-0.74. A weaker though highly significant negative regression was seen in sugar metabolism (26 genes, R(2) = 0.66) and myofiber proteins (42 genes, R(2) = 0.54). Among individual genes that showed a strong association with firmness, there were extracellular matrix proteins (negative correlation), immune genes, and intracellular proteases (positive correlation). Several genes can be regarded as candidate markers of flesh quality (coiled-coil transcriptional coactivator b, AMP deaminase 3, and oligopeptide transporter 15) though their functional roles are unclear. To conclude, fillet firmness of Atlantic salmon depends largely on metabolic properties of the skeletal muscle; where aerobic metabolism using lipids as fuel, and the rapid removal of damaged proteins, appear to play a major role.